2000
DOI: 10.1042/cs0980449
|View full text |Cite
|
Sign up to set email alerts
|

Venous reflux has a limited effect on calf muscle pump dysfunction in post-thrombotic patients

Abstract: The purpose of the present study was to evaluate the relationship between calf muscle pump dysfunction (CMD) and the presence and location of valvular incompetence. Deep vein obstruction might influence CMD, and so venous outflow resistance (VOR) was measured. VOR and calf muscle pump function were measured in 81 patients, 7-13 years after venographically confirmed lower-extremity deep venous thrombosis. The supine venous pump function test (SVPT) measures CMD, and the VOR measures the presence of venous outfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It has been unclear how much these different mechanisms are interdependent. In this issue of Clinical Science, Haenen and co-workers [6] examined the relationship between venous reflux, measured by duplex ultrasound, calf muscle pump function, measured by the supine venous pump function test (SVPT), and obstruction to venous outflow, measured by venous outflow resistance, in patients up to 13 years after lower limb DVT. They found that there was no relationship between the location and extent of venous reflux and calf muscle pump efficacy, although there was a tendency for calf muscle pump function to be impaired in those patients with the most widespread reflux.…”
Section: Chronic Venous Insufficiency In Post-thrombotic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been unclear how much these different mechanisms are interdependent. In this issue of Clinical Science, Haenen and co-workers [6] examined the relationship between venous reflux, measured by duplex ultrasound, calf muscle pump function, measured by the supine venous pump function test (SVPT), and obstruction to venous outflow, measured by venous outflow resistance, in patients up to 13 years after lower limb DVT. They found that there was no relationship between the location and extent of venous reflux and calf muscle pump efficacy, although there was a tendency for calf muscle pump function to be impaired in those patients with the most widespread reflux.…”
Section: Chronic Venous Insufficiency In Post-thrombotic Patientsmentioning
confidence: 99%
“…In the presence of varicose veins there is increased venous compliance [19] and reduced ejection of calf venous volume [20]. As yet undefined, and not discussed in the report by Haenen et al [6], is whether some of the changes observed in calf muscle pump function in the setting of varicose veins may actually be consequent on a primary varicose vein disorder rather than secondary to past DVT. Furthermore, although the current study indicates that calf muscle pump dysfunction is an independent risk factor for the development of chronic venous insufficiency after DVT [6], it must be borne in mind that there is a secondary interaction that occurs whereby chronic venous insufficiency changes themselves reduce the range of movement of the ankle and thus the function of the calf muscle pump [7].…”
Section: Calf Muscle Pump Dysfunctionmentioning
confidence: 99%